EFFECT OF INTRAVENOUS VERSUS INTRATHECAL DEXMEDETOMIDINE ON CHARACTERISTICS OF HYPERBARIC BUPIVACAINE SPINAL ANESTHESIA IN LOWER LIMB SURGERY - Senapati, Laxman K; Samanta, Priyadarsini (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Dexmedetomidine was shown to prolong the duration of spinal anesthesia and enhance post-operative analgesia. The aim of the study was to compare the effect of intravenous (IV) versus intrathecal (IT) administration of dexmedetomidine on bupivacaine spinal anesthesia in patients undergoing lower limb surgery. Methods: A prospective randomized controlled study was conducted during the year 2014–15. 60 American Society of Anesthesiologists physical status I–II aged 18–60 years scheduled for lower limb surgery under spinal anesthesia were assigned randomly to two groups: (1) IT group (IT group) (n=30) patients received 3 ml of 0.5% hyperbaric bupivacaine and 5 μg of dexmedetomidine intrathecally (100 μg/1 ml ampoule drawn in 40 IU/ml insulin syringe making 5 μg=2 IU=0.05 ml) and (2) IV group (IV group) (n=30) received 3 ml of 0.5% hyperbaric bupivacaine and 0.05 ml of normal saline intrathecally followed 5 min later by IV dexmedetomidine 0.5 μg/kg by infusion pump over 10 min as a single dose. Results: The IT group had a statistically significantly earlier sensory onset to T10 and shorter time from injection to highest sensory level (p<0.001). The regression times of two dermatomes, regression time to S1 dermatome and time to reach Bromage 3 motor block were significantly less in the IT group, whereas regression time to Bromage 0 was prolonged (p<0.001). The IT group showed a significantly longer time to the use of rescue analgesia and less analgesic consumption in first 24 h than the IV group (p<0.001). Furthermore, the intensity of pain was significantly less in the IT group as compared to IV group (p<0.001). Compared with IV group, the IT group had low sedation score, fewer overall side effects, which was statistically not significant (p>0.05). Conclusion: In bupivacaine spinal anesthesia for limb surgeries, dexmedetomidine, when administered intrathecally, has greater augmentation to sensory and motor block, more hemodynamic stability, better analgesic properties, and fewer overall side effects compared to the IV route of administration.